2018
DOI: 10.1101/262295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AnoniMME: Bringing Anonymity to the Matchmaker Exchange Platform for Rare Disease Gene Discovery

Abstract: Advances in genome sequencing and genomics research are bringing us closer to a new era of personalized medicine, where healthcare can be tailored to the individual's genetic makeup, and to more effective diagnosis and treatment of rare genetic diseases. Much of this progress depends on collaborations and access to genomes, thus, a number of initiatives have been introduced to support seamless data sharing. Among these, the Global Alliance for Genomics and Health runs a popular platform, called Matchmaker Exch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Data sharing is essential for advancing biomedical research. However, large-scale data sharing has been limited, primarily due to privacy concerns [12], [22], [2], [24]. Homer et al [16] have shown that an adversary can effectively predict the presence of an individual in a genomic dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Data sharing is essential for advancing biomedical research. However, large-scale data sharing has been limited, primarily due to privacy concerns [12], [22], [2], [24]. Homer et al [16] have shown that an adversary can effectively predict the presence of an individual in a genomic dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Oprisanu and De Cristofaro propose a privacy-enhanced version [56] of the Matchmaker Exchange (MME) platform [10]. More specifically, they rely on Reverse Private Information Retrieval (PIR) to allow researchers to query a gene within the MME platform anonymously.…”
Section: Related Workmentioning
confidence: 99%